Effect of Emotion Labeling-based Training on Behavioral Disorders of Children With Autism Spectrum Disorder - Vahid Moradi; Somayeh Sohrabi; Hossein Rashki Ghaleno; Shima Haghani (Iran University of Medical Sciences, 2023)
Background & Aims Evidence has shown that the inability to regulate and understand emotions causes various behavioral problems in children with autism spectrum disorder (ASD). This study aims to investigate the effect of an emotion labeling (EL)-based training on the behavioral disorders of children with ASD. Materials & Methods This is a quasi-experimental single-subject study ABA method. Five boys with high-functioning autism were purposefully included in the study after one week of sampling in 2022. For each child, the Let's Face It software was used individually to recognize basic emotion expressions (6 types) in three sessions followed by teaching EL at 8 sessions for 4 weeks, two sessions per week. The data collection tool was a demographic form and the test of behavioral disorders of children with ASD. The collected data at five phases were analyzed in SPSS software, using descriptive statistics, and Friedman's test. Results According to the result of Friedman test, there was a significant difference between the first and third phases (P=0.037) and the third and fourth phases (P=0.019) of behavioral disorders measurement. The EL training significantly reduced the behavioral disorders of patients (P=0.030). Conclusion It seems that the EL-based training can reduce the behavioral disorders of children with ASD.